2016
DOI: 10.5657/kfas.2016.0367
|View full text |Cite
|
Sign up to set email alerts
|

Maturity and Spawning of the Marbled Flounder Pseudopleuronectes yokohamae off the Coast of Pohang, East Sea

Abstract: Pleuronectes yokohamae , Pseudopleuronectes yokohamae (Ji et al., in press).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the present study, MMP of 1-year cryopreserved sperm using extender-1 combined with 15% Me 2 SO or 12% GLY showed a significant value similar to MMP values of 7-day cryopreserved sperm and those of fresh sperm. Kim et al ( 2016 ) reported the effects of long-term (3-year) cryopreservation on MMP of seven-band grouper. However, the present study demonstrated that post-thaw motility of cryopreserved sperm was similar to that of fresh sperm, which could explain the absence of difference in MMP between fresh and sperm cryopreserved (7 days and 1 year) using extender-1 + 15% Me 2 SO or extender-1 + 12% GLY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, MMP of 1-year cryopreserved sperm using extender-1 combined with 15% Me 2 SO or 12% GLY showed a significant value similar to MMP values of 7-day cryopreserved sperm and those of fresh sperm. Kim et al ( 2016 ) reported the effects of long-term (3-year) cryopreservation on MMP of seven-band grouper. However, the present study demonstrated that post-thaw motility of cryopreserved sperm was similar to that of fresh sperm, which could explain the absence of difference in MMP between fresh and sperm cryopreserved (7 days and 1 year) using extender-1 + 15% Me 2 SO or extender-1 + 12% GLY.…”
Section: Discussionmentioning
confidence: 99%
“…Although aquaculture technology for this species has been developed in Japan (Lucas et al, 2019 ), it has not been reported from other countries yet. Gonadal maturity occurs earlier in males than in females of this species (Kim et al, 2016 ), making its hatchery production difficult. Cryopreserved sperm can solve this problem by supplying sperm during hatchery production (Hassan et al, 2017 ; Gheller et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%